Prediction Competition Result of Indonesian Football Club with C.45 Algorithm - Gde Brahupadhya Subiksa; Made Dinda Pradnya Pramita; Komang Oka Saputra (International Journal of Engineering and Emerging Technology, 2018)
Indonesia is a country that is very fond of soccersport, according to Gojek-Traveloka League data there are anaverage of 13,423 spectators watching every game. With a sizeableaudience and a fairly regular schedule of matches by clubs andleagues in Indonesia. It makes predictions interesting because itwill provide an overview and direction of support for thecompeting club. In some studies relating to predictions anddecisions recommending the use of excessive C4.5 methods oralgorithms, such as the C4.5 algorithm can produce decision treesthat are easy to interpret, have an acceptable level of accuracy,efficient in dealing with discrete type attributes and can handleattribute of discrete and numeric type. So based on theexplanation, this research will discuss about the prediction ofIndonesian football club match using C4.5 method based on gamehistory that has been done before. The purpose of this research isto know how far C4.5 method can be applied in predicting soccermatch. The results of this study indicate that the C4.5 algorithmcan be implemented in predictions of the results of the gameproved with a fairly good accuracy of 63.04%.